2011
DOI: 10.1519/jsc.0b013e31820f50ef
|View full text |Cite
|
Sign up to set email alerts
|

Strongmen Sport is Associated with Larger Absolute Heart Size and Impaired Cardiac Relaxation

Abstract: This study was carried out to compare cardiac structure and function and blood lipids among Strongmen, sedentary controls, and marathoners. Echocardiography was performed, and endothelial function, blood lipids and maximal oxygen uptake were measured in 27 Caucasian adult men (8 Strongmen, 10 marathoners, 9 controls). Absolute cardiac size parameters such as left ventricular (LV) diameter and wall thickness of Strongmen were higher (p < 0.05), but relative (body surface area indexed) parameters were not differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
5
9
2
Order By: Relevance
“…In the current study, LV mass of dynamic and static athletes was significantly greater than that in nonathletes. This finding was previously reported by Abinader et al26 and D’Andrea et al3 Although the current study did not result in a difference between static and dynamic athletes with regard to LV mass, Venckunas et al indicated that LV mass was lower in static athletes compared with dynamic athletes 7. During dynamic exercise, the LV withstands repetitive stress, which leads to an increase in LV mass.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, LV mass of dynamic and static athletes was significantly greater than that in nonathletes. This finding was previously reported by Abinader et al26 and D’Andrea et al3 Although the current study did not result in a difference between static and dynamic athletes with regard to LV mass, Venckunas et al indicated that LV mass was lower in static athletes compared with dynamic athletes 7. During dynamic exercise, the LV withstands repetitive stress, which leads to an increase in LV mass.…”
Section: Discussionsupporting
confidence: 82%
“…Global diastolic LV function was normal as well, which in contrary to the report on Strongmen who perform very intense resistance training and avoid aerobic training (30). Global diastolic function (assessed as E/A ratio) has been reported to be normal in female athletes from other resistance type of sports (9).…”
Section: Discussioncontrasting
confidence: 60%
“…In this study 11 of 100 athlete participants show an increase in left ventricle enddiastolic dimension (<58mm). The study carried out by Venckunas detected that there is a close correlation between the increase in the size of the heart and exercise (Venckunas et al, 2011).…”
Section: Discussionmentioning
confidence: 93%